Mabs for treating asthma: omalizumab, mepolizumab, reslizumab, benralizumab, dupilumab - Erminia Ridolo; Francesco Pucciarini; Maria Cristina Nizi; Eleni Makri; Paola Kihlgren; Lorenzo Panella; Cristoforo Incorvaia (Taylor & Francis Group, 2020)
The introduction of biologics for the treatment of patients with refractory asthma represented a marked therapeutic advance. For more than 10 y, the only biologic available has been the monoclonal anti-IgE antibody omalizumab, reserved for patients with asthma caused by perennial allergen. In recent years, other biologics have been licensed for the treatment of severe eosinophilic asthma. They include monoclonal antibodies that target the Th2-pathway cytokines, such as IL-5 (mepolizumab and reslizumab) or its receptor (benralizumab) and the IL-4 and IL-13 receptor (dupilumab). The effectiveness of these biologics was demonstrated in several placebo controlled trials, the main outcomes being the significant reduction of the rate of asthma exacerbation and the improvement of respiratory function in actively treated patients. Based on the further understanding of the pathogenesis of asthma, new cytokines network and new targets are emerging, such as thymic stromal lymphopoietin, which can activate Th2 cells, innate lymphoid cells, or both, or prostaglandin D2 (PGD2), to develop additional biologics.